A longitudinal dataset of retrenched automotive workers in Australia - Jacob Irving; Andrew Beer; Sally Weller; Tom Barnes; Ilke Onur; Julie Ratcliffe; David Bailey; Markku Sotarauta; Akshay Vij (Scientific Data)
Abstract The closure of Australia’s automotive manufacturing industry in 2017 marked a significant economic shift, leading to widespread job losses across Original Equipment Manufacturers and supply chain firms. This paper presents a consolidated dataset from all five waves of a longitudinal study tracking the long-term outcomes of retrenched automotive workers from 2020 to 2024. The study collected data on employment status, job history, household circumstances, financial well-being, and labour market experiences, reflecting the diverse pathways taken by participants post-retrenchment. A total of 4,261 responses were collected over five waves, providing critical insights into the impacts of industry closures on affected workers and their communities. Data collection employed a combination of Computer-Assisted Telephone Interviews and online surveys, targeting retrenched autoworkers primarily from South Australia and Victoria. This dataset contributes a robust resource for researchers and policymakers seeking to understand the socio-economic effects of large-scale industry transitions and to inform future strategies for supporting displaced workers.